Correlation Of Nutritional Status, Physical Activity, Protein, and Magnesium Intake with Muscle Endurance Among College Students - Purwaningtyas, Desiani Rizki; Herawati, Lala Diana; Fitriani, Anna (Universitas Negeri Semarang, 2024)
Muscular endurance is included in the components of fitness related to health. Good muscular endurance is important for college students to reduce muscle fatigue so they can do activities including studying longer. The purpose of this study was to analyze the correlation between nutritional status, protein intake, magnesium, and physical activity with muscle endurance. This study is a quantitative study using a cross-sectional design. The sampling technique used was purposive sampling concerning predetermined criteria and a sample of 99 students in Jakarta was obtained. The instruments in this study used a weighed food record, a physical activity recall form, and a push-up and wall squat muscle endurance test form. The Pearson and Spearman correlation tests analyzed the relationship between independent and dependent variables. Most of the respondents had poor and very poor muscle endurance both based on push-ups (96%) and wall squat tests (79,8%). The majority of respondents had good nutritional status (57.6%), insufficient protein intake (56.6%), insufficient magnesium intake (98%), and light physical activity level (93.9%). Nutritional status, protein intake, magnesium, and physical activity were not significantly correlated with muscle endurance in college students (p-value> 0.05).